Analisis Tindakan Pemerintahan Daerah Kabupaten Bandung Barat Terhadap Perusahaan Yang Tidak Memberikan Kesempatan Kerja Bagi Pekerja Lokal - Mutierly Sulastri; Agus Mulya Karsona; Holyness N Singadimedja (Fakultas Hukum Universitas Islam Batik Surakarta, 2023)
This study aims to find out and analyze the government's actions towards companies that do not prioritize local workers as an effort to provide job opportunities for local workers in West Bandung Regency. This type of research uses a normative juridical approach with qualitative juridical analysis. The research location is at the West Bandung District Employment Service. Types and sources of data in research consists of two types, primary data and secondary data. Data collection techniques are by observation techniques, interviews, and literature study. Qualitative data analysis techniques. The results of the study show that West Bandung Regency has indeed regulated the company's obligation to prioritize local workers in filling job vacancies in order to provide job opportunities for local workers in West Bandung Regency, but these arrangements have not been able to be implemented optimally. This is caused by several things, including the limited ability of existing local workers, the large role of companies in the West Bandung Regency area, as well as policies regarding companies that are required to prioritize local workers are not accompanied by a comparison of the use of local workers and sanctions if the policy is not implemented.